Orienting Fate: Spatial Regulation of Neurogenic Divisions - Wang, Xiaoqun; Lui, Jan H.; Kriegstein, Arnold R. (Neuron (Cambridge, Mass.), 2011)
Cleavage plane orientation has been thought to govern the fate of neural stem cell progeny, but supporting evidence in the neocortex has been sparse. A new study by Postiglione et al. in this issue of Neuron shows that mouse Inscuteable-mediated control of cleavage plane orientation regulates the output of neural progenitor cells.